Analysis of Halal Value Chain Growth in Indonesia through the Halal Pharmaceutical and Cosmetics Industry in 2019-2023 - Baiduri Hayatun Nufus, Alifa; Zaidan Irfanudin, Naufal; Khoerunnisa, Hana; Yonita, Meli (Devotion : Journal of Research and Community Service, 2025)
The growth of the halal industry in Indonesia is experiencing rapid expansion, driven by the increasing demand from Muslim consumers and government policy support. The halal pharmaceutical and cosmetic sectors are two key industries that significantly contribute to the strengthening of the Halal Value Chain in the country. This research aims to analyze the impact of the growth of these two sectors on the strengthening of the Halal Value Chain in Indonesia. This research is based on the increasing public awareness of the importance of halal certification, as well as the high demand for halal products in both domestic and global markets. This research focuses on measuring the contribution of the growth of the halal pharmaceutical and cosmetic industry to the strengthening of the halal value chain, using a quantitative approach with secondary data through a literature study. The results of this study indicate that the halal pharmaceutical and cosmetic industry has an influence on the growth of the halal value chain.